6p valence relativistic effects in 5d photoemission spectrum of Pb atom and bonding properties of Pb-dimer using Dirac–Hartree–Fock formalism including many-body effects - Bagus, Paul S.; Suzer, Sefik (Journal of vacuum science & technology. A, Vacuum, surfaces, and films, 2022)
There has been strong recent interest related to the large spin–orbit coupling in Pb monolayers on various properties of graphene and other 2D-materials. The underlying physical/chemical origin of the spin–orbit splitting has been discussed in terms of the valence 6p atomic level of the lead atom. Indeed, the photoelectron spectra of the Pb atom were the subject of investigations about 50 years ago in Dave Shirley’s laboratory at UC Berkeley. In a paper published in 1975, using He-I UV photoelectron spectroscopy, we reported an unexpected relative intensity ratio for the observed atomic Pb peaks (2P1/2 and 2P3/2) after removal of a 6p valence electron and attributed it to the large spin–orbit interaction in that level. In this contribution, we use the Dirac–Hartree–Fock formalism to reanalyze the complex spectral features reported five years later, for the 5d He-II UV photoelectron spectrum of atomic lead, to extract the 6p valence contribution, which turns out to be significant. Furthermore, we calculate the energy levels of the Pb-dimer at the experimental equilibrium geometry of the molecule to also find the significant contribution of the spin–orbit splitting of the atomic 6p levels in the composition of the valence molecular orbitals of the dimer. Such an approach can be extended to larger systems like monolayers containing lead or other heavy atoms, thus helping in designing 2D-materials with controlled and better targeted properties.